(untitled) (International Journal of Engineering and Computer Science, 2017)
The cloud computing and the Internet of things are tightly coupled with each other . The rapid growth of the Internet of Things (IoT) and the development of technologies created a widespread connection of “things”. This results in the production of large amounts of data which needs to be stored, processed and accessed. Cloud computing is a paradigm for big data storage and analytics while the Internet of Things is exciting on its own that the real innovation will come from combining it with cloud computing . This can enable sensing services and powerful processing of sensing data stream. More things are being connected to address a growing range of business needs. In fact, by the year 2020, more than 50 billion things will connect to the Internet—seven times our human population. Insufficient security will be a critical barrier to large-scale deployment of IoT systems and broad customer adoption of IoT applications using cloud. Simply extending the existing IT security architectures to the IoT and cloud will not be sufficient. The IoT world requires new security approaches, creating fertile ground for innovative thinking and solutions. This paper discusses key issues that are believed to have long-term significance in IoT and cloud computing security and privacy, based on documented problems and exhibited weaknesses